Quaternary of South America and Antarctic Peninsula.
1 online resource.
Keywords: This book focuses on the problems of the Quaternary in South America and Antarctic Peninsula, with a strong emphasis in the paleoenvironmental and paleoclimatic approach. It is based on contributions presented at the South American Regional Meeting held in Neuquen, Argentina.